Healing High‐Risk Sternotomy Incisions: Interrupted Suture Closure and Negative Pressure Wound Therapy. Issue 4 (18th June 2014) - Said, Sameh M.; Daly, Richard C.
Abstract High‐risk sternotomy incisions represent a challenge at the time of wound closure. We present an alternate wound closure technique that can be used in high‐risk sternotomy incisions and consists of a combination of space‐obliterating sutures and negative pressure (suction using wound VAC) therapy. doi: 10.1111/jocs.12388 (J Card Surg 2015;30:346–350)